Effect of Certain Nutrients on Fruit Set, Fruit Retention, Physical Characters and Yield of Ber Fruit (Zizyphus mauritiana Lamk). cv. Banarasi Karaka - Singh, Vikas Kumar; Shanker, Karuna; Tiwari, N. K.; Rao, O. P. (International Journal of Bio-resource and Stress Management, 2023)
The present investigation was undertaken on the effect of certain nutrients on fruit setting, fruit retention, physical characters and yield of ber fruit (Zizyphus mauritiana Lamk). c.v. Banarasi Karaka at main experiment station, Department of Horticulture, Narendra Deva University of Agriculture and Technology Kumarganj, Faizabad (U.P.) during the years 2008–2009. Plants received uniform cultural operations throughout the experimental period. Treatments included control, Ferrous sulphate (FeSO4) @ 0.3%, Ferrous sulphate @ 0.6%, Potassium sulphate (K2SO4) @ 1.0%, Potassium sulphate @ 2.0%, borax (Na2B4O7 10H2O ) @ 0.5%, borax @ 1.0%, (FeSO4 @ 0.3%+K2SO4 @ 1.0%+borax @ 0.5%, (FeSO4 @ 0.6%+K2SO4 @ 2.0%+borax @ 1.0%. The nutrients were sprayed as aqueous solutions using Tween-20 as a surfactant. First spray was done in month of September just before flowering and second spray was done after fruit setting. The results were found that the foliar spray of FeSO4 @ 0.6%, along with K2SO4 @ 2%, and borax @ 1.0%, proved most effective in recording maximum initial fruit setting, fruit retention, minimum fruit drop, and maximum length and breath, stone weight of fruit, pulp stone ratio and weight of fruit which contributed to maximum yield. The better fruit quality parameters viz. % of TSS, sugar, ascorbic acid, lowest acidity was also recorded with the application of the same treatment.